Adaptive web service selection based on data type matching for dynamic web service composition - Ramasamy, R Kanesaraj; Fang, Fang Chua; Su, Cheng Haw; Chin, Kuan Ho (2015)
Although there are many web services provided for access in World Wide Web (WWW), some services are not available at all times.It is very important to ensure all services are available when a service composition takes place.A web service that meets the requirements of the workflow but does not match the data type will still cause a failure in composition.To address this concern, we propose an adaptive web service selection method which is able to replace a current web service which has been used for composition but fails during execution time.The proposed algorithm will select the most appropriate web service based on web service discovery engine recommendation and match the requirement based on WSDL description. Upon matching the requirements of the workflow, the selected web service will be matched according to the input and output data type. The goal of this paper is to ensure every web service that meets the requirements of the workflow does not get rejected when the data type does not fulfill the matching criteria.